Proses Rebranding MGo Shuttle Menjadi Lintas Shuttle - M. Fauzi Ramadhan; Yanti Setianti; Ade Kadarisman (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
MGo Shuttle management decided to rebrand, they changed the overall MGo brand identity. One of them is by changing the name, namely Lintas Shuttle. The company's decision to conduct a rebranding began with the bankruptcy of the parent company, namely PT. Citra Maharlika Nusantara Corpora. finally the son of this holding company, PT. Citra Maharlika Lintas Wahana (CMLW)